EFEKTIVITAS PENGGUNAAN CHATGPT SEBAGAI SCAFFOLDING DIGITAL DALAM PEMECAHAN MASALAH MATEMATIKA: SYSTEMATIC LITERATURE REVIEW - Desiviana, Fani; Fatah, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) has brought various innovations to the field of education, one of which is the use of ChatGPT as digital scaffolding in mathematics learning. This study aims to analyze the effectiveness of using ChatGPT as digital scaffolding in supporting mathematical problem-solving skills. The method used is a Systematic Literature Review (SLR) by examining articles obtained from the Google Scholar and Scopus databases using relevant keywords. Based on the selection process according to the inclusion and exclusion criteria, 10 articles were obtained and analyzed descriptively and qualitatively. The results of the review indicate that ChatGPT has a positive impact on mathematics learning, particularly in improving conceptual understanding, problem-solving skills, learning motivation, and student independence. ChatGPT is able to function as digital scaffolding by providing concept explanations, solution hints, practice problems, and feedback gradually according to students’ needs. In addition, the use of ChatGPT creates a more interactive and flexible learning experience. However, several challenges need to be considered, such as the potential dependence on technology and the possibility of inaccurate answers for certain problems. Therefore, the role of teachers remains necessary to guide the use of ChatGPT so that it can be utilized optimally in mathematics learning. Thus, ChatGPT has significant potential as digital scaffolding to support students’ mathematical problem-solving abilities